Dengue virus serotypes and genotypic characterization from northeast India. Issue 6 (15th February 2019) - Chetry, Sumi; Khan, Siraj A.; Dutta, Prafulla; Apum, Basumoti; Medhi, Pranita S.; Saikia, Durlov C.; Temsu, Temjen; Mawii, Lalhming; Marak, Bichitrani C.
Abstract: Dengue is a rapidly spreading acute arboviral infection transmitted through a human and Aedes mosquito cycle. Though northeast region of India has been experiencing dengue outbreaks regularly for over a decade, reports on genetic characterization of the virus from this region are limited. The present study was undertaken to detect the genotype and genetic composition of circulating dengue virus (DENV) in this region. Blood samples were collected from 918 suspected dengue patients of five northeast Indian states. Serological investigations, viz, nonstructural 1 (NS1) enzyme‐linked immunosorbent assay (ELISA), immunoglobulin M (IgM) ELISA, and immunoglobulin G (IgG) ELISA were performed followed by molecular detection. Sequence analysis and phylogenetic tree construction based on capsid‐premembrane (C‐prM) gene junction was done by BioEdit and MEGA6 software, respectively. Serological detection showed 35.34% NS1 and 18.12% IgM positivity. Secondary infection was observed in 24.53%. All four serotypes were detected. Phylogenetic analysis demonstrated circulation of genotype III of DENV‐1, genotype IV of DENV‐2, and genotype III of DENV‐3. Sequences from this region form distinct clades in the phylogenetic tree. Characterization of the C‐prM gene junction reveals divergence among the DENV strains. As genetic variation within the DENV is known to be associated with diverse clinical outcomes, information regarding the genetic composition of circulating virus could be beneficial in designing an effective intervention strategy. Highlights: All four DENV serotypes are circulating in northeast India. Gentoype‐III of DENV‐1, Genotype‐IV of DENV‐2 and Genotype‐III of DENV‐3 were detected during the study.